Flexible thinking as a function of predicting the performance of the Iraqi Premier League referees' football - Adday, Ali Sabah; Aideem, Najm Abbas; JEBUR, HABEEB SHAKER (International Journal of Psychosocial Rehabilitation, 2020)
Referee performance during match management is linked to referees' mental processes for most of the match and it is known that the performance of refereeing in football relates to the principle of flexible thinking. There is no doubt that the decision-making by the referees in the match must be coordinated and that the referee understands and expects all actions within the field of play.Accordingly, the main objectives of the research were as follows: Know the relationship between the referee’s performance and the flexible thinking of football referees of the Iraqi Premier League.Know the percentage of the contribution of flexible thinking in the performance of the referee's football for the Iraqi Premier League.Predicting the performance of the soccer referees' in the Iraqi Premier League in terms of flexible thinking.To achieve these goals, the researchers used the descriptive method with its survey method and the study of correlational relationships, while the research tools were the football officials of the Iraqi Premier League, who number (50) referee, as well as means of data collection. . . After a series of field procedures represented in ensuring the validity of the flexible thinking scale, the researchers began research procedures, and using the appropriate statistical means to address the results in a way that serves the research and achieves the goals. The performance of referees' is related to a meaningful relationship with flexible thinking